Journal Writing Errors of Senior High School Students - Sumipo, Jasmin M. (International Journal of English Literature and Social Sciences (IJELS), 2019)
This study aimed to help senior high school students achieve deftness in writing in terms of grammatical correctness. Likewise, this study sought to find out the common journal errors of the students with the hope of designing instructional modules to improve the students’ written ability. Error analysis method was used in this study. The journal entries of the total population of students enrolled in Reading and Writing classes served as the sources of data. The common errors in the areas of journal format construct, content and style, lexico- syntactic structure, and correct mechanics and punctuation, were noted and tabulated. Analysis and interpretation were then made based on these errors. The results showed that the students used either meta-cognitive or reflective formats. With regard to content and style, outputs revealed the use of simple sentences in paragraphs and violation on the principles of unity and coherence. Majority of the students committed errors on the lexico-syntactic structure. Capitalization and spelling were the most frequent errors in the students’ written composition; this only showed lapses in the observance of correct mechanics and punctuation. The researcher concluded that the reading and writing students lack the writing competence expected of senior high school learners as shown on the errors in their journal entries. In fact, written entries were hardly comprehensible at times due to the varied lapses on correct writing conventions.